Penguatan Literasi Dasar Melalui Model Pembelajaran Kontekstual dan Problem Based Learning di Daerah Minim Akses Digital - Agung, Suari; Sukra Suantari, Kadek; Anggariyanti, Luh; Eka Octavia Darmayanti, Ni Putu; Ayu Made Meirayanti, Gusti; Dedi Juniarta, Komang (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Literacy is a fundamental prerequisite for developing students’ academic competencies. However, the 2022 PISA survey revealed that Indonesian students’ reading literacy remains low, especially in remote areas such as SDN 4 Sembiran, which faces limited internet access and challenging socio-economic conditions. This community service aims to improve basic literacy skills through an integrated learning approach combining contextual teaching and problem-based learning, based on students’ ability grouping. The method involved eight literacy training sessions supported by participatory observation and formative evaluation. Results showed significant progress in students’ ability to recognize letters, write, read syllables, words, simple sentences, and comprehend texts. More advanced students were able to read short passages, answer text-based questions, and compose simple paragraphs. The main challenges were pronunciation of consonant clusters and mastery of silent letters, which were gradually overcome with consistent guidance and adaptive methods. This program highlights the importance of ability-based grouping, integration of contextually relevant teaching methods, and active literacy facilitation. Approaches linking learning materials to real-life contexts and problem-solving effectively enhanced students’ motivation and literacy skills in remote areas. Structured and sustainable learning strategies are key to successfully improving basic literacy across varying student abilities.